Чужелюбие revisited - Bobrik, Marina (Wiener Slawistischer Almanach, 2025)
The history of the word chuzheliubie in Russian is largely unclear. This word has not been included in dictionaries, and its use can be traced only partially. In the 1930s it was used by Mandelstam in his prose about Armenia, for whom, as Omry Ronen has shown, the notion of chuzheliubie was essential and had a purely positive humanistic meaning. Having found no other evidence of usage, Ronen assimilates chuzheliubie in his essays as a word from Mandelstam’s vocabulary. However, this word has a prehistory, the outline of which will be reconstructed in the article. Of great significance in the semantic evolution of the word chuzheliubie is the reception of biblical sources. Not only related words and cognates of the word (in Hebrew, Greek, German) could be found, but also earlier contexts of its use in Russian literature. These contexts are connected with the discourse of European national conservatism and are semantically different from Mandelstam’s usage.